Modulation of Suppressive Activity and Proliferation of Human Regulatory T Cells by Splice-Switching Oligonucleotides Targeting FoxP3 Pre-mRNA - Blinova, Varvara G.; Gladilina, Yulia A.; Abramova, Anna A.; Eliseeva, Daria D.; Vtorushina, Valentina V.; Shishparenok, Anastasia N.; Zhdanov, Dmitry D. (Cells (Basel, Switzerland), 2023)
The maturation, development, and function of regulatory T cells (Tregs) are under the control of the crucial transcription factor Forkhead Box Protein 3 (FoxP3). Through alternative splicing, the human FoxP3 gene produces four different splice variants: a full-length variant (FL) and truncated variants with deletions of each of exons 2 (∆2 variant) or 7 (∆7 variant) or a deletion of both exons (∆2∆7 variant). Their involvement in the biology of Tregs as well as their association with autoimmune diseases remains to be clarified. The aim of this work was to induce a single FoxP3 splice variant in human Tregs by splice switching oligonucleotides and to monitor their phenotype and proliferative and suppressive activity. We demonstrated that Tregs from peripheral blood from patients with multiple sclerosis preferentially expressed truncated splice variants, while the FL variant was the major variant in healthy donors. Tregs with induced expression of truncated FoxP3 splice variants demonstrated lower suppressive activity than those expressing FL variants. Reduced suppression was associated with the decreased expression of Treg-associated suppressive surface molecules and the production of cytokines. The deletion of exons 2 and/or 7 also reduced the cell proliferation rate. The results of this study show an association between FoxP3 splice variants and Treg function and proliferation. The modulation of Treg suppressive activity by the induction of the FoxP3 FL variant can become a promising strategy for regenerative immunotherapy.